2021
DOI: 10.4018/ijkm.2021070103
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing in Catholic Organizations

Abstract: This study examines knowledge sharing in Catholic organizations. The authors adopt Schein's organizational culture theory that facilitates, or inhibits, knowledge sharing in organizations. Thus, they address the phenomenon at the three levels: the artifacts, the norms and values, and the underlying assumptions. Considering the chosen settings, they study the contributions of individuals having taken vows, the organizational rituals, the significance, and the sense of community perceived by the organizational m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The total number of authors identified in the articles was 140, with most articles having more than one author (Table 3). Articles with two or more authors may generate more relevant contributions due to the exchange of knowledge between the authors (Curado, Oliveira, & Maçada, 2011).…”
Section: Bibliometric Findingsmentioning
confidence: 99%
“…The total number of authors identified in the articles was 140, with most articles having more than one author (Table 3). Articles with two or more authors may generate more relevant contributions due to the exchange of knowledge between the authors (Curado, Oliveira, & Maçada, 2011).…”
Section: Bibliometric Findingsmentioning
confidence: 99%
“…e asymmetry of causality means that the presence or absence of an effect requires different "causal combinations" to be explained separately [38]. If the reasons for success and failure are different, the opposite of the reason for success cannot simply be used to explain failure [47]. Conditioning asymmetry means that a given cause, when combined with some conditions, may have a positive effect on the outcome, and when combined with other conditions, it may have a negative effect.…”
Section: Results Analysismentioning
confidence: 99%
“…Complex solutions propose all possible combinatorial conditions based on traditional logical operations. However, since the number of determined configurations may be very large, the number of complex solutions may be large, which makes the interpretation of the solutions quite difficult [47]. erefore, we generally further simplify the complex solutions into simplified solutions and intermediate solutions.…”
Section: Configuration Analysismentioning
confidence: 99%
See 1 more Smart Citation